Missio Dei dalam Konteks Indonesia: Analisis Naratif Matius 18:15-17 sebagai Misi Allah bagi Gereja - Hanry Chandra; Grant Nixon; Martina Novalina (KHARISMATA: Jurnal Teologi Pantekosta, 2021)
The Church is a fellowship of the sinners who have accepted Jesus Christ as Lord and saviour. Ironically, even after receiving forgiveness of sin, congregations are still human beings who still have the potential to do sin or mistake. It can happen to anyone, whether he is a church member, servant, or even pastor. Besides that, sin and mistake can happen in multiple forms and places, internally or externally. This article itself is an effort to find a biblical formulation in order to face this reality within the church ministry. This formulation can be found within Matthew 18:15-17 which contains a special discourse in Matthew concerning the church. The Church often understands Missio Dei or God’s mission only for non-Christian. According to this research, by using a descriptive-analytical method toward Matthew 18:15-17, which is a proportional hermeneutic approach, there seems a concept that Missio Dei also goes to Christians who live in sin. God loves sinners and because of that, He arranges how a Christian community faces its members who did sin. In this case, Matthew 18:15-17 teaches a concept that Missio Dei happens in multidimensional, including the one who has known God, yet falls in sin again.AbstrakPemahaman Missio Dei yang terlalu terpusat pada gereja cenderung menempatkan sasarannya atas bangsa-bangsa yang belum terjangkau Injil atau daerah-daerah yang belum pernah dijelajah. Hal ini menyebabkan perhatian Missio Dei sangat dominan pada usaha kon-versi. Mereka yang telah terhisab dalam gereja dipandang sebagai “yang telah ditemukan”, sehingga tidak lagi menjadi sasaran utama dalam pembahasan misi. Padahal penekanan pada usaha konversi semacam ini dapat menjadi tantangan tersendiri dalam misi konteks Asia, terutama Indonesia. Melalui penelitian dengan menggunakan metode deskriptif analitis terhadap Matius 18:15-17, yaitu melalui pendekatan hermeneutik yang proporsional, ditemukan suatu konsep bahwa Missio Dei berlaku juga bagi mereka yang sudah Kristen namun jatuh dalam dosa. Allah mengasihi orang berdosa dan oleh sebab itu, Ia mengatur bagaimana komunitas Kristen menghadapi jemaat yang berbuat dosa. Dengan kata lain, teks Matius 18:15-17 mengajarkan satu konsep bahwa Missio Dei berlaku dalam berbagai dimensi, termasuk bagi orang-orang Kristen yang sudah mengenal Allah, namun berbuat dosa lagi.